264 FREEDOM AND LONELINESS: SPOUSAL DEMENTIA CARE-GIVERS AND THE NURSING HOME TRANSITION. (25th October 2022) - Power, JM; Holton, E; Warters, A; Simons, R; Pertl, M; O'Sullivan, R; O'Philbin, L; Lawlor, B
Abstract: Background: Many persons with dementia transition to nursing home care, but little is known about the impact, positive and negative, that this may have on the social isolation and loneliness of their spouse. Methods: Using our existing theoretical synthesis of loneliness to provide sensitising concepts, we conducted a deductive grounded theory study of loneliness during the nursing home transitions. We recruited 11 spousal participants to engage in semi-structured remote interviews during 2021. Results: Participants provided their own definitions of loneliness, and spoke about their life history of loneliness, the loneliness associated with living with a spouse with dementia, and the loneliness, and alleviation of loneliness through re-engagement with social contacts, associated with their spouse moving to the nursing home. Participants agreed with the idea that loneliness has a physical feeling. More distal parts of the theoretical synthesis, such as the influence that culture and gender have on loneliness, were not corroborated by the findings. Conclusion: We conclude that loneliness is a frequent experience among spousal caregivers whose spouse has moved to nursing home care, but that loneliness is also associated with living with a spouse with dementia. Loneliness in this population was aggravated by the COVID-19 pandemic and associated lockdowns. Further research steps will involve more targeted interviewing to focus on the link between transitions and loneliness in this and in other populations.